Wood-based super-hydrophobic graphene electric heating composite material and preparation method thereof

By performing flame retardant treatment of wood materials and laser processing embedded in the graphene layer, and then covering the soot carbon particles, the complex and cost-effective preparation process of conductive wood is solved, the excellent electrothermal properties and superhydrophobic properties of the material are achieved, and maintenance is reduced Cost and maintain long-term stable performance.

CN119212138APending Publication Date: 2024-12-27CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411442515.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, the preparation process of conductive wood is complex and costly, making it difficult to achieve excellent conductivity and superhydrophobic properties while keeping the wood dry.

Method used

By performing flame retardant treatment on the wood substrate material and using laser processing to construct a groove array pattern of micro-nano structures, embedded a graphene layer, and then covering the soot carbon particles to form a wood-based superhydrophobic graphene electrothermal composite material.

Benefits of technology

The excellent electric and superhydrophobic properties of the material are achieved, the maintenance costs are reduced, the material performance remains stable for a long time, and has self-cleaning performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119212138A_ABST
    Figure CN119212138A_ABST
Patent Text Reader

Abstract

The invention discloses a wood-based super-hydrophobic graphene electric heating composite material and a preparation method thereof. The preparation method comprises the following steps: S1, carrying out flame retardant treatment on a wood-based material, and drying to obtain a flame-retardant base material; s2, a continuous groove array pattern with a micro-nano structure is constructed on the surface of the flame-retardant substrate material in a laser processing mode, and the conductive wood material with the micro-nano structure embedded with graphene on the surface is obtained; s3, smoke carbon particles are deposited on the surface of the conductive wood material through the outer flame of the combusted paraffin material, and the wood-based super-hydrophobic graphene electric heating composite material is obtained. After laser processing and smoke carbon deposition, the surface of the continuous wood-based super-hydrophobic graphene electric heating composite material with the groove array patterns of the micro-nano structure has excellent electric heating performance and simple and efficient self-cleaning performance, the maintenance cost of the material is greatly reduced, and the service life of the material is prolonged. And the material performance output can be kept at a relatively fixed level for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrothermal composite materials, and in particular to a wood-based super-hydrophobic graphene electrothermal composite material and a preparation method thereof. Background Art

[0002] Wood materials are composed of various carbon-containing molecules and non-carbon-containing molecules (such as wood fiber and bast fiber), most of which are susceptible to moisture and have strong hygroscopicity. Conductive wood is a material that has light weight, high conductivity and high electromagnetic shielding properties, while also exhibiting excellent mechanical properties.

[0003] There are many methods to improve the conductivity of wood materials, such as delignification, conductive filler, and metal electrochemical deposition. However, delignification may weaken the structure of wood, making it more fragile and the processing process is more complicated; conductive fillers (such as carbon nanotubes) are generally expensive, and because wood itself is anisotropic, there will be problems of uneven filling; metal electrochemical deposition requires some special chemical treatment to introduce metal into wood, which is more demanding on equipment. At the same time, keeping wood dry while achieving strong conductivity remains a challenge.

[0004] In general, the preparation process of conductive wood currently has problems such as being cumbersome, requiring complex reaction equipment or being expensive, the wood has high hygroscopicity and is easily affected by moisture, and it is difficult for excellent electrothermal properties and super-hydrophobic properties to coexist.

[0005] In view of this, it is necessary to propose a wood-based super-hydrophobic graphene electrothermal composite material and a preparation method to solve the above-mentioned defects. Summary of the invention

[0006] The main purpose of the present invention is to provide a method for preparing a wood-based super-hydrophobic graphene electrothermal composite material, which has no restrictions on the entity material, is simple to operate and has low cost, thereby overcoming the shortcomings of the prior art.

[0007] To achieve the above object, the present invention provides a method for preparing a wood-based super-hydrophobic graphene electrothermal composite material, comprising the steps of:

[0008] S1, performing flame retardant treatment on the wood base material to obtain a flame retardant base material;

[0009] S2, using laser processing to construct a continuous groove array pattern with micro-nano structure on the surface of the flame-retardant base material, to obtain a conductive wood material with micro-nano structure of graphene embedded on the surface;

[0010] S3, depositing soot particles on the surface of the conductive wood material in step S2 to cover the micro-nano structure embedded with graphene, so as to obtain the wood-based super-hydrophobic graphene electrothermal composite material.

[0011] Furthermore, the wooden base material is a cork material.

[0012] Furthermore, the wooden base material is one of oak bark and Quercus acutissima.

[0013] Furthermore, in step S3, a continuous groove array pattern with a micro-nano structure is constructed on the surface of the flame-retardant base material by the outer flame of the burning paraffin material.

[0014] Furthermore, the laser processing method includes: focusing a laser beam on the surface of the flame-retardant base material, and processing the surface of the base material by laser direct writing.

[0015] Furthermore, in the laser processing method, the repetition frequency of the laser processing is 300-600kHz, the pulse width of the laser processing is 350fs, the wavelength of the laser processing is 1035nm, the processing speed of the laser processing is 10-200mm / s, and the output power of the laser processing is 1-2W.

[0016] Furthermore, the continuous groove array pattern includes one or a combination of stripe patterns, spiral patterns, arc patterns, and cross-tic-tac-toe patterns.

[0017] Furthermore, the continuous groove array pattern includes a first stripe pattern and a second stripe pattern, and the first stripe pattern and the second stripe pattern are perpendicular to each other to form a cross-shaped cross pattern.

[0018] Furthermore, the size of the microstructure in the micro-nanostructure is 30-60 μm, and the size of the nanostructure is 1-100 nm.

[0019] Furthermore, the step S1 specifically includes immersing the wooden base material in a flame retardant for 24 to 36 hours, and then drying to obtain the flame retardant base material; wherein the flame retardant is a nitrogen-phosphorus flame retardant.

[0020] The present invention also provides a wood-based super-hydrophobic graphene electrothermal composite material, wherein the wood-based super-hydrophobic graphene electrothermal composite material is prepared by the preparation method of the wood-based super-hydrophobic graphene electrothermal composite material as described in any one of the above items.

[0021] Compared with the prior art, the present invention provides a wood-based super-hydrophobic graphene electrothermal composite material and a preparation method thereof, comprising the steps of: S1, flame retardant treatment of a wood-based base material to obtain a flame retardant base material; S2, using laser processing to construct a continuous groove array pattern with a micro-nano structure on the surface of the flame retardant base material to obtain a conductive wood material with a micro-nano structure embedded with graphene on the surface; S3, soot particles are deposited on the surface of the conductive wood material in step S2 to cover the micro-nano structure embedded with graphene to obtain the wood-based super-hydrophobic graphene electrothermal composite material. After laser processing and soot deposition, the surface of the wood-based super-hydrophobic graphene electrothermal composite material with a continuous groove array pattern with a micro-nano structure has excellent electrothermal performance and simple and efficient self-cleaning performance, which greatly reduces the maintenance cost of the material and enables the material performance output to be maintained at a relatively fixed level for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 These are scanning electron microscope images of the surfaces of materials obtained in different steps of Example 1 of the present invention, wherein a is a scanning electron microscope image of the surface of the oak bark material, b is a scanning electron microscope image of the surface of the oak bark material after laser processing, and c is a scanning electron microscope image of the surface of the oak bark material after candle burning treatment after laser processing.

[0023] Figure 2 ] are water contact angle diagrams of the surfaces of the materials obtained in different steps of Example 1 of the present invention, wherein a is a water contact angle diagram of the surface of the oak bark material before laser processing, b is a water contact angle diagram of the surface of the oak bark material after flame retardant treatment, and c is a water contact angle diagram of the surface of the oak bark material after laser processing and candle burning treatment.

[0024] Figure 3 1 is the surface electrothermal performance test result of the wood-based super-hydrophobic graphene electrothermal composite material in Example 1 of the present invention, a is the curve of the average surface temperature curve of the material changing with the voltage gradient, and b is the average surface temperature curve of the material under different voltages.

[0025] Figure 4 This is the long-term electrothermal performance test result of the average surface temperature of the wood-based super-hydrophobic graphene electrothermal composite material at a voltage of 10V in Example 1 of the present invention.

[0026] Figure 5 These are the test results of the electrothermal performance of the surface of the wood-based super-hydrophobic graphene electrothermal composite material in Example 1 of the present invention before being covered with dust, after being covered with dust, and after being cleaned.

[0027] Figure 61 is the Raman test result of the wood-based super-hydrophobic graphene electrothermal composite material in Example 1 of the present invention, a is the Raman test result made on the flame-retardant substrate material after laser processing, and b is the Raman test result made on the flame-retardant substrate material after laser processing and candle burning treatment. DETAILED DESCRIPTION

[0028] The technical solution in this embodiment will be described clearly and completely below in conjunction with the drawings in this embodiment. Obviously, the described embodiment is only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In addition, the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0030] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0031] Please refer to Figure 1-Figure 2 The present invention provides a method for preparing a wood-based super-hydrophobic graphene electrothermal composite material, comprising the steps of:

[0032] S1, performing flame retardant treatment on the wood base material to obtain a flame retardant base material;

[0033] S2, using laser processing to construct a continuous groove array pattern with micro-nano structure on the surface of the flame-retardant base material, to obtain a conductive wood material with micro-nano structure of graphene embedded on the surface;

[0034] S3, depositing soot particles on the surface of the conductive wood material in step S2 to cover the micro-nano structure embedded with graphene, so as to obtain the wood-based super-hydrophobic graphene electrothermal composite material.

[0035] Wood materials are composed of various carbon-containing molecules and non-carbon-containing molecules (such as wood fibers and bast fibers), most of which are susceptible to moisture and have strong hygroscopicity. In step S1, the wood base material is subjected to flame retardant treatment and dried to obtain a flame retardant base material. In the subsequent step S3, during the deposition of soot particles, the wood will not be burned or damaged due to excessive temperature due to the high temperature resistance of the graphene layer itself and the flame retardant effect of the base. At the same time, when the electric heating properties of the composite material are used, the wood will not be burned or damaged due to the generation of electric heat.

[0036] As a non-contact advanced processing technology based on thermal energy, laser processing technology is known as the "universal processing tool of the 21st century". Laser processing has been successfully applied to many fields such as metals, ceramics, and plastics with its high efficiency and high precision. In particular, the great contribution of laser processing technology in improving the surface chemical properties of wood materials, including traditional laser cutting, laser engraving, laser heat treatment, etc., as well as emerging surface modification and regulation of internal structure, provides a multi-level and multi-angle optimization approach for wood. In step S2, a continuous groove array pattern with a micro-nano structure is constructed on the surface of the flame-retardant base material by laser processing, so as to obtain a conductive wood material with a micro-nano structure and a graphene layer on the surface. Specifically, the electrical conductivity and electrothermal properties of the wood-based super-hydrophobic graphene electrothermal composite material are mainly generated in this step. By processing the surface of the flame-retardant base material with specific laser processing parameters, a groove with a micro-nano structure can be formed. The wood material in the groove will be carbonized to form graphene attached to the groove after laser processing; by laser scanning, a continuous groove array pattern with a micro-nano structure is formed, so that the surface of the flame-retardant base material has a certain conductivity, thereby obtaining the corresponding electrothermal properties.

[0037] The soot produced by the incomplete combustion of paraffin materials such as candles is a cheap and efficient super-hydrophobic coating material, which has excellent super-hydrophobicity in the air and excellent thermal stability and chemical stability. Through step S3, the outer flame of the burning paraffin material is used to deposit soot particles on the surface of the conductive wood material in step S2 to obtain the wood-based super-hydrophobic graphene electrothermal composite material. Specifically, in step S3, the laboratory can use the outer flame of the candle to experiment the deposition of soot particles; in industrial production, in addition to the deposition of soot particles produced by burning paraffin, a variety of methods can also be used. Chemical vapor deposition uniformly deposits carbon particles by high-temperature decomposition of carbon-containing gases (such as methane), which is suitable for large-scale precise control. The pyrolysis method generates a carbon layer by heating the organic material for pyrolysis, which is economical and efficient and suitable for large-scale production. Plasma enhanced chemical vapor deposition (PECVD) decomposes the carbon source by plasma at low temperature, which is gentle and efficient. The sputtering deposition rule deposits carbon particles by ion bombardment of a carbon target, which is commonly used in precision manufacturing.

[0038] The surface of the processed wood-based super-hydrophobic graphene electrothermal composite material exhibits super-hydrophobic and electrothermal properties. The base material can be made of wood or cork material, and the material cost is low.

[0039] Furthermore, the wooden base material is a cork material.

[0040] Furthermore, the wooden base material is one of oak bark and Quercus acutissima.

[0041] Furthermore, the laser processing method includes: focusing a laser beam on the surface of the base material, and processing the surface of the base material by laser direct writing.

[0042] Further, in the laser processing method, the repetition frequency of the laser processing is 300-600kHz, the pulse width of the laser processing is 350fs, the wavelength of the laser processing is 1035nm, the processing speed of the laser processing is 10-200mm / s, and the output power of the laser processing is 1-2W. It should be understood that the laser processing parameters can be adjusted according to the actual situation and the selected materials.

[0043] Preferably, the range of laser processing parameters can also be selected as follows: repetition frequency of 300-400kHz, pulse width of 200fs, wavelength of 1035nm, processing speed of 10-100mm / s, output power of 1-2W.

[0044] Furthermore, the continuous groove array pattern includes one or a combination of stripe patterns, spiral patterns, arc patterns, and cross-tic-tac-toe patterns.

[0045] Furthermore, the continuous groove array pattern includes a first stripe pattern and a second stripe pattern, and the first stripe pattern and the second stripe pattern are perpendicular to each other to form a cross-shaped cross pattern.

[0046] Furthermore, the size of the microstructure in the micro-nanostructure is 30-60 μm, and the size of the nanostructure is 1-100 nm.

[0047] Furthermore, the step S1 specifically includes immersing the wooden base material in a flame retardant for 24 to 36 hours, and then drying to obtain the flame retardant base material; wherein the flame retardant is a nitrogen-phosphorus flame retardant, the main component of which is phosphate.

[0048] The present invention also provides a wood-based super-hydrophobic graphene electrothermal composite material, wherein the wood-based super-hydrophobic graphene electrothermal composite material is prepared by the preparation method of the wood-based super-hydrophobic graphene electrothermal composite material as described in any one of the above items.

[0049] The present invention is described below with reference to specific experimental data and embodiments.

[0050] Example 1

[0051] (1) Providing an oak bark base material with a thickness of 5 mm;

[0052] (2) The oak bark base material is immersed in a flame retardant (a flame retardant whose main component is phosphate) for 24 to 36 hours to perform flame retardant treatment, and then dried to obtain the flame retardant base material;

[0053] (3) using a laser processing method to process a micro-nano structure on the surface of the oak bark by laser direct writing, and then using a candle flame to burn each part of the surface of the laser-processed micro-nano structure for 1 to 2 seconds to obtain a wood-based super-hydrophobic graphene electrothermal composite material; wherein the laser processing parameters are: pulse width of 350 fs, pulse repetition frequency of 200 kHz, central wavelength of 1035 nm, output power of 2 W, scanning spacing of 70 μm, and processing speed of 10 mm / s;

[0054] Experimental results:

[0055] Please combine Figure 1 , Figure 1 -a is a scanning electron microscope image of the surface of the oak bark base material in Example 1. Before laser processing, the surface of the oak bark is relatively flat and has a large number of honeycomb mesh structures. Figure 1 -b is a scanning electron microscope image of the surface of the oak bark base material in Example 1 after laser processing. Figure 1 -c is a scanning electron microscope image of the surface of the oak bark base material in Example 1 after laser processing and candle burning treatment.

[0056] Figure 1 -c It can be seen that the micro-nano structure processed on the surface of the oak bark base material is covered with nano-scale candle smoke carbon particles, and the size of these nano-scale particles is 1 to 10nm.

[0057] Please combine Figure 2 , take a certain amount of deionized water, add a drop of deionized water on the surface of the substrate material, and use a high-temperature wetting angle meter to measure the water contact angle. Figure 2 -a, the water contact angle of the oak bark base material is 139°; Figure 2 -b, the water contact angle of the flame retardant base material after flame retardant treatment is 47.6°; Figure 2 -c, the water contact angle of the wood-based super-hydrophobic graphene electrothermal composite material after laser processing and candle burning is 151.2°. It can be seen that the surface of the processed wood-based super-hydrophobic graphene electrothermal composite material exhibits super-hydrophobic properties, which provides a good condition for maintaining the stability of electrothermal performance and reduces the maintenance cost of the material.

[0058] Please combine Figure 3 , the wood-based super-hydrophobic graphene electrothermal composite material was made into an electrothermal device and then connected to a DC voltage source. The voltage of the DC voltage source was set to 2, 4, 6, 8, and 10 V in sequence. After 5 minutes of power supply at each voltage, it was directly switched to the next voltage. The surface temperature of the material was observed and recorded with an infrared thermal imager, and the temperature-time curve was plotted, as shown in Figure 3 -a as shown.

[0059] according to Figure 3-a shows the temperature-time curve. After connecting to 2, 4, 6, 8, and 10 V voltages in sequence, the surface temperature of the wood-based superhydrophobic graphene electrothermal composite material can rise to 262.2 °C, showing superhydrophobicity and excellent electrothermal performance.

[0060] The above results show that the surface of the wood-based superhydrophobic graphene electrothermal composite material with micro-nano structure after laser processing and candle burning has excellent electrothermal performance, and has simple and efficient self-cleaning performance, which greatly reduces the maintenance cost of the material and enables the material performance output to be maintained at a relatively fixed level for a long time.

[0061] The wood-based super-hydrophobic graphene electrothermal composite material is made into an electrothermal device and then connected to a DC voltage source, the voltage of which is set to 2, 4, 6, 8, and 10 V in sequence, and the power is turned off after being powered on for 5 minutes at each voltage, and the next voltage is connected when the material cools to the initial temperature, and the surface temperature of the material is observed and recorded with an infrared thermal imager, and a temperature-time curve is drawn;

[0062] like Figure 3 -b, according to the temperature-time curve, under a voltage of 10V, the surface temperature of the material can rise to 262.2℃ within 30 seconds.

[0063] The wood-based super-hydrophobic graphene electrothermal composite material was made into an electrothermal device and then connected to a DC voltage source. The voltage of the DC voltage source was set to 10V, and the power was continuously turned on for 25 minutes. The surface temperature of the material was observed and recorded with an infrared thermal imager, and a temperature-time curve was drawn.

[0064] like Figure 4 As shown, according to the temperature-time curve, under a voltage of 10V, the surface temperature of the material can be stabilized at 257.3~267.6℃ within 25 minutes.

[0065] Please combine Figure 5 , the wood-based super-hydrophobic graphene electrothermal composite material was made into an electrothermal device and then connected to a DC voltage source. The voltage of the DC voltage source was set to 4V, and the power was continuously turned on for 5 minutes. The surface temperature of the material was observed and recorded with an infrared thermal imager; the power was turned off, and the 4V voltage was continued to be connected after the surface of the material was covered with dust. The surface temperature of the material was observed and recorded with an infrared thermal imager; the power was turned off, the material was tilted 3-20°, and deionized water was dropped on the surface of the material to allow the water to take away the dust. After the dust was cleaned, the 4V voltage was continued to be connected, and the surface temperature of the material was observed and recorded with an infrared thermal imager.

[0066] like Figure 5 As shown, the material can initially heat up to 71.3°C at 4V, but when it is covered with dust, the measured temperature is 58.5°C. However, after self-cleaning, the surface temperature is measured again to 69.8°C, close to the original value.

[0067] The micro-nano structure of the wood-based super-hydrophobic graphene electrothermal composite material is continuous, and the addition of soot can also conduct electricity continuously. The soot only covers the surface of the structure. A small amount of carbon atoms embedded in the graphene layer will increase the resistance of the graphene layer, but the experimental results show that the electrothermal performance is enhanced instead, because whether the Joule heating effect is enhanced is not completely determined by the size of the conductivity, Q = I 2 R=U 2 / R, U remains unchanged, although I decreases and R increases, the positive gain of the Joule thermal effect due to the increase in resistance is greater than the negative effect of the current reduction, so the electrothermal performance is enhanced.

[0068] Please refer again Figure 6 , Raman testing was performed on the wood-based super-hydrophobic graphene electrothermal composite material. The results of the Raman test showed that graphene existed; at the same time, there was also porous carbon material generated by laser processing. Therefore, the conductivity should be due to the combined effect of graphene generated by laser processing and porous carbon material, mainly graphene.

[0069] In summary, after verification, it can be seen that this material can be used as an electric heating device with self-cleaning function and has stable performance.

[0070] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a wood-based super-hydrophobic graphene electrothermal composite material, characterized in that: Includes steps: S1, performing flame retardant treatment on the wood base material to obtain a flame retardant base material; S2, using laser processing to construct a continuous groove array pattern with micro-nano structure on the surface of the flame-retardant base material, to obtain a conductive wood material with micro-nano structure of graphene embedded on the surface; S3, depositing soot particles on the surface of the conductive wood material in step S2 to cover the micro-nano structure embedded with graphene, so as to obtain the wood-based super-hydrophobic graphene electrothermal composite material.

2. The method for preparing the wood-based super-hydrophobic graphene electrothermal composite material according to claim 1, wherein The wooden base material is a cork material.

3. The method for preparing the wood-based super-hydrophobic graphene electrothermal composite material according to claim 2, wherein: The wooden base material is one of oak bark and Quercus acutissima.

4. The method for preparing the wood-based super-hydrophobic graphene electrothermal composite material according to claim 1, wherein: In step S3, a continuous groove array pattern with a micro-nano structure is constructed on the surface of the flame-retardant base material by the outer flame of the burning paraffin material.

5. The method for preparing the wood-based super-hydrophobic graphene electrothermal composite material according to claim 1, characterized in that, The laser processing method includes: focusing a laser beam on the surface of a flame retardant base material, and processing the surface of the base material by laser direct writing; wherein the repetition frequency of the laser processing is 300 to 600 kHz, the pulse width of the laser processing is 350 fs, the wavelength of the laser processing is 1035 nm, the processing speed of the laser processing is 10 to 200 mm / s, and the output power of the laser processing is 1 to 2 W.

6. The method for preparing the wood-based super-hydrophobic graphene electrothermal composite material according to claim 1, characterized in that: The continuous groove array pattern includes one or a combination of stripe pattern, spiral pattern, arc pattern, and cross-tic-tac-toe pattern.

7. The method for preparing the wood-based super-hydrophobic graphene electrothermal composite material according to claim 6, characterized in that: The continuous groove array pattern includes a first stripe pattern and a second stripe pattern, and the first stripe pattern and the second stripe pattern are perpendicular to each other to form a cross-shaped cross pattern.

8. The method for preparing the wood-based super-hydrophobic graphene electrothermal composite material according to any one of claims 1 to 7, characterized in that: The size of the micron structure in the micro-nano structure is 30-60 μm, and the size of the nano structure is 1-100 nm.

9. The method for preparing the wood-based super-hydrophobic graphene electrothermal composite material according to claim 1, characterized in that: The step S1 specifically includes immersing the wooden base material in a flame retardant for 24 to 36 hours, and then drying to obtain the flame retardant base material; wherein the flame retardant is a nitrogen-phosphorus flame retardant.

10. A wood-based super-hydrophobic graphene electrothermal composite material, characterized in that: The wood-based super-hydrophobic graphene electrothermal composite material is prepared by the preparation method of the wood-based super-hydrophobic graphene electrothermal composite material according to any one of claims 1 to 9.